Impact of living with a bilateral central vision loss due to geographic atrophy—qualitative study - Rajiv Raman; Shahina Pardhan; Raju Sapkota; S Ve Ramesh; Gopinath Madheswaran (BMJ Open)
Objective Geographic atrophy (GA), a type of dry age-related macular degeneration, affects vision as central vision loss (CVL). The challenges faced due to bilateral CVL in activities of daily living and strategies taken to overcome those challenges are not very well understood in the Indian population. This qualitative study aims to understand the impact on everyday life activities and related adaptive and coping strategies in people with long-standing bilateral CVL due to GA in India.Design, participants, setting and methods A qualitative study using a semistructured face-to-face interview was conducted on 10 people with bilateral CVL after obtaining written informed consent. The interviews were audio-recorded, and were transcribed verbatim. Thematic analysis was carried out to understand the challenges faced and adaptive methods due to the impact of CVL.Results Ten participants (50% male) with a median age (IQR) of 72 (70, 74) years were interviewed. All the participants had best-corrected visual acuity of ≤6/60 in the better eye and reported an absolute central scotoma with the home Amsler chart. Qualitative thematic analysis identified four main themes: challenges in everyday living (difficulty in face identification, reading), challenges with lifestyle and socialisation (driving, cooking, reading for a longer duration, watching TV, socially inactive), psychological implications (depression, poor self-esteem, fear due to poor vision) and strategies to overcome the challenges (voice identification, technology support).Conclusion GA has a severe negative impact on the quality of life in people with CVL. Inability to recognise faces was the main reason for dependency on others and being socially disconnected. The findings will help clinicians in providing improved rehabilitative care.